The housekeeper : a novel - Dainty, Suellen (Washington Square Press, 2017)
"I am the housekeeper, the hired help with a messy past who cleans up other people's messy lives, the one who protects their messy little secrets." When Anne Morgan's successful boyfriend--who also happens to be her boss--leaves her for another woman, Anne finds herself in desperate need of a new job and a quiet place to recover. Meanwhile, her celebrity idol, Emma Helmsley (England's answer to Martha Stewart), is in need of a housekeeper, an opportunity which seems too good to be true. Through her books, website, and blog, Emma Helmsley advises her devoted followers on how to live a balanced life in a hectic world. Her husband, Rob, is a high profile academic, and her children, Jake and Lily, are well-adjusted teenagers. On the surface, they are the perfect family. But Anne soon finds herself intimately ensconced in the Helmsley's dirty laundry, both literally and figuratively. Underneath the dust, grime, and whimsical clutter, everyone has a secret to hide and Anne's own disturbing past threatens to unhinge everything. For fans of Notes on a Scandal and The Woman Upstairs, The Housekeeper is a nuanced and nail-biting psychological thriller about the dark recesses of the human mind and the dangerous consequences of long-buried secrets"--